2007
DOI: 10.1161/hypertensionaha.107.097006
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Antioxidant and Vasodilatory Action of Carbon Monoxide in Angiotensin II–Induced Cardiac Hypertrophy

Abstract: Abstract-The aim of this study was to determine the effects of carbon monoxide (CO) at a nontoxic low concentration on the cardiac and vascular hypertrophic response and reactive oxygen species generation, compared with the action of a vasodilator, hydralazine. Twelve-to 16-week-old low-density lipoprotein receptor knockout mice were subjected to angiotensin II (Ang II) infusion using osmotic minipumps (Ang II group; nϭ11) for 2 weeks. Controls were administered saline (nϭ10). Animals were exposed to CO in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…CO also has antiapoptotic 2) and anti -inflammatory 3) potentials. In addition, we showed previously that CO also had antioxidative behavior 13) . Tobacco smoking is an important source of CO as a pollutant 15) .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…CO also has antiapoptotic 2) and anti -inflammatory 3) potentials. In addition, we showed previously that CO also had antioxidative behavior 13) . Tobacco smoking is an important source of CO as a pollutant 15) .…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, the vasodilatation properties of CO, which also has anti -apoptotic and anti -in-CARBON MONOXIDE ELEVATES IN ISCHEMIC HEART flammatory potentials 2,3) , have been investigated in the cardiovascular system 12) . We previously reported that synergetic antioxidant and vasodilatory action of carbon monoxide attenuated angiotensin IIinduced cardiac hypertrophic change 13) . Although the cytoprotective roles of CO has been investigated by in vitro studies using CO releasing molecules (11) and in vivo studies using high exogenous CO exposure 14) , the behavior of CO under pathophysiological conditions is still unknown.…”
Section: Introductionmentioning
confidence: 98%
“…2,18 One limitation with CO inhalation is the high levels of blood carboxyhemoglobin (COHb) that are achieved at CO levels (200 to 500 ppm) required to ensure significant increases in tissue levels of CO. 19,20 These effects on blood COHb levels may limit the clinical applicability of CO inhalation unless lower levels of CO can achieve similar results. In support of this idea, a recent study by Kobayashi et al 21 demonstrated that low-level CO inhalation (60 ppm), which did not result in a dramatic increase in blood COHb levels, was able to significantly attenuate the development of angiotensin II (Ang II)-dependent hypertension. This study provides the first evidence that chronic low level CO inhalation may be a viable option for the treatment of hypertension.…”
Section: Altering Co Levels In Vivo: Tools Of the Tradementioning
confidence: 94%
“…This statement is especially true for CO, because levels as low as 800 ppm in the air can be fatal. However, a growing body of literature indicates that low-level CO inhalation (Ͻ100 ppm) or treatment with CO donors has several beneficial cardiovascular actions, including lowering of blood pressure, 21 protection against cardiac ischemia, 1,93 and protection against diabetes induced vascular injury. 25 There are also substantial reports that induction of HO-1, which results in increased CO production, also lowers blood pressure in several forms of hypertension.…”
Section: Perspectivesmentioning
confidence: 99%
“…Kobayashi et al 15 studied the effects of carbon monoxide (CO) because it reduces O 2 Ϫ and may ameliorate the pro-oxidant effects of Ang II. In Ang II-infused mice, CO administered for 2 hours per day attenuated the rise in BP and left ventricular hypertrophy compared with Ang II controls.…”
Section: Ang Ii-o 2 ؊ Effects In the Heartmentioning
confidence: 99%